Atendimento educacional especializado no contexto da política de educação especial da rede pública municipal de São Luís/MA: complexidades, movimentos e desafios - ARAÚJO, Gisele Maria (2016)
Educational policy in the perspective of inclusive education has been implemented in Brazilian educational systems. Resolutions, decrees, technical notes and government programs follow the guidelines of national policy. The Special Education, through the normative documents, advocates the Specialized Educational Service in a complementary and supplementary way, to its target audience that happens in the Multifunctional Resource Rooms. In this context, the implementation and organization of this service of Special Education to have visibility. The purpose of this research is to investigate how the actions are being carried out and how the Specialized Educational Assistance in the context of the Special Education Policy in the Municipal Public Education Network of São Luís materializes. National, state and municipal levels of public power over Specialized Educational Assistance (AEE); To apprehend the process of implantation of the room of Multifunctional Resource Room in the context of the National Policy of Special Education and its implications in the Municipal Network of São Luís; (7) teachers of multifunctional resource rooms of municipal schools of São Luís-MA, 07 (seven) managers and the superintendent of Special Education of São Luis totaling 15 (subjects). The semi-structured interview was adopted as a data collection instrument and the data were analyzed by the content analysis method (BARDIN 1977). The study was based on the contributions of authors such as: Melo (2008); Carvalho (2012); Jesus (2012); Garcias (2008); Kassar (2012); Martins (2008), among others. The results indicate that the implementation and organization of the Multifunctional Resource Rooms in the municipal network of São Luís-Ma fracture as to its materialization regarding the training of teachers, maintenance of technological resources and support professionals (caregivers), despite the efforts of the technical team The Superintendency of Special Education of Luís-MA and the professionals inserted in the context.